Timber growth, cacao yields, and financial revenues in a long-term experiment of cacao agroforestry systems in northern Honduras - Ramírez-Argueta, Oscar; Orozco-Aguilar, Luis; Dubón, Aroldo Dubón; Díaz, Francisco J.; Sánchez, Jesús; Casanoves, Fernando (Frontiers in Sustainable Food Systems, 2022)
Cacao in Honduras is cultivated under traditional shade tree species (Inga sp., Erythrina sp., Gliricidia sp.), fruit and timber species deliberately planted or selected and managed from natural regeneration. Typically, the shade canopy of these cacao plantations is poorly managed resulting in high tree density and heavy shading, thus affecting cacao yield performance overtime. We assessed 12 cacao plots made up of 15–35 useful timber shade trees with varying spacing 6 × 9, 9 × 9, 8 × 10, and 10 × 12 m. Initially, each plot consisted of three shade components plus cacao. Plantain (Musa x paradisiaca) and madreado (Gliricidia sepium) were used as temporary shade and timber species, were selected as permanent shade. Dasometric data were retrieved to assess growth rates of timber species and cacao yield per plant were recorded to explore the effects of shade cover yield performance and the incidence of main diseases. Specifically, we: a) calculated growth rates and build curves for diameter (DBH), total height (Ht), and commercial volume (Vc) and compared the growing performance with ANOVA and DGC tests; b) run a correlation analysis between shade cover, timber basal area, cocoa yields, and the incidence of monilia and black pod. Statistical differences were found in terms of growth rates among timber species evaluated. Mean annual growth rates were 2.25 cm in DBH, 1 m in Ht, and the standing commercial timber gained was 4.2 m3ha−1year−1. Cocoa yields ranged between 950 and 1,365 kg ha1year1 and were negatively affected by both increased tree cover and timber basal area. Cacao yields were reduced up to 25% when tree cover and tree basal area were over 40% and 10 m2ha−1, respectively. Regardless of timber tree species, no significant effect of tree cover was found on the incidence of cacao diseases. After 22 years, total revenues were determined by the proportion of incomes provided by each component of the agroforestry systems assessed. Five out of 12 timber-based cacao plantations accumulated more than U$95,000 of combined revenues, equivalent to incomes of US$3775 ha−1 year−1. Timber-based cacao plantations are a promising alternative for farm diversification in northern Honduras.